Influence of Thermal Radiation and MHD on the Boundary Layer Flow Due to an Exponentially Stretching Sheet - Abda Ameer, Nidhal (Iraqi Journal of Science, 2023)
In this paper, the effect of thermal radiation and magnetic field on the boundary layer flow and heat transfer of a viscous fluid due to an exponentially stretching sheet is proposed. The governing boundary layer equations are reduced to a system of ordinary differential equations. The homotopy analysis method (HAM) is employed to solve the velocity and temperature equations.